Comparison of Hydrus and iStent microinvasive glaucoma surgery implants in combination with phacoemulsification for treatment of open-angle glaucoma: systematic review and network meta-analysis. Issue 6 (15th June 2022) - Hu, Rongrong; Guo, Dongyu; Hong, Nan; Xuan, Xiuyuan; Wang, Xiaoyu
Abstract : Objectives: To compare the efficacy and safety of two Schlemm's canal-based microinvasive glaucoma surgery (MIGS) devices, the Hydrus Microstent and the iStent Trabecular Bypass combined with phacoemulsification for treatment of open-angle glaucoma. Design: Systematic review and network meta-analysis. Methods: Literature searches were conducted on PubMed, Web of Science, Cochrane Library and ClinicalTrials.gov to identify randomised controlled trials (RCTs) assessing the Hydrus or the iStent implantation combined with phacoemulsification for treatment of open-angle glaucoma until September 2020. Risk of bias was assessed using a six-item modified Jadad scale. Effects were estimated using the intraocular pressure (IOP) reduction (IOPR), the percentage of IOPR and the proportion of medication-free patients at follow-up end. Safety was estimated using the proportions of adverse events. The network meta-analysis was conducted within a Bayesian framework using the Markov Chain Monte Carlo method in ADDIS software. Results: Six prospective RCTs comprising 1397 patients were identified. Regarding the absolute value and the percentage of IOPR, the Hydrus and 2-iStent implantation combined with phacoemulsification were significantly more effective than phacoemulsification alone. Rank probability analysis revealed the Hydrus might be the best choice to lower IOP. There was no significant difference in the proportion of medication-free patients among groups. The Hydrus and 2-iStent implantation had a higher probability to achieve the medication-free status versus the 1-iStent implantation and phacoemulsification alone. Overall safety profiles were good for each device with the focal peripheral anterior synechiae more frequently reported in Hydrus eyes. Conclusions: The Hydrus implantation may have a slight advantage over the 1-iStent or 2-iStent implantation in combination with phacoemulsification to treat open-angle glaucoma. Our findings might be of some uncertainty due to the limited included data. Further studies are needed to investigate whether our findings are robust, including high-quality RCTs to directly compare these MIGS devices.